Average sampling and reconstruction for signals in shift‐invariant subspaces of weighted mixed Lebesgue spaces. (29th March 2021) - Wang, Suping; Zhang, Jiaxing
Abstract : In this paper, we mainly study the average sampling problem for signals in a shift‐invariant subspace of weighted mixed Lebesgue space. First, the sampling stability for two kinds of average sampling functionals is established. Then, two iterative reconstruction algorithms with exponential convergence are presented for recovering the shift‐invariant signals from the corresponding average samples.